Determinants of Commitment and Job Satisfaction among Faculty in Higher Education - Dangan, Shirley (JPAIR Institutional Research, 2025)
Faculty members are the front-line employees of any higher education institution who directly impact the successful implementation of the institution's vision, mission, and goals. Therefore, studying the organizational factors that may influence their organizational behavior is essential. This study examined the relationships between the faculty's self-reported commitment and job satisfaction and their perceptions of organizational support, climate, and justice in the university. It aimed to provide research-based information that may guide policy-makers in formulating policies that promote commitment and job satisfaction. This quantitative research used a survey questionnaire with a reliability index of 0.91. A total of 203 or 69% of Palawan State University, Puerto Princesa City, Philippines, served as respondents. In compliance with research ethics, the researcher ensured the respondent's voluntary participation and the anonymity and confidentiality of data.  Based on the regression model, POJ (B=0.329, p
Keywords: Commitment; Job Satisfaction; State Universities; Faculty; Work-Related Variables; quantitative; Philippines